Characterization of 3-D collagen hydrogels for functional cell-based biosensing - Mao, Chen; Kisaalita, William S. (Biosensors and Bioelectronics, 2004)
To address the growing demand for functional cell-based assay technologies with accelerated drug discovery applications, we have proposed the use of human neuroblastoma cells (IMR-32) immobilized in three-dimensional (3-D) collagen hydrogel matrices. The gel protects weakly adherent cells from fluid mechanical forces while providing a more physiologically relevant 3-D environment. Hydrogels made up of collagen, between 0.5 and 1.0mg/ml, exhibited mechanical stability adequate to withstand fluid mechanical forces (<0.11mN) typical of automated commercial fluid transfer equipment. Collagen-entrapped cells visualized with the aid of confocal microscopy and a potentiometric-sensitive dye, TMRM, exhibited round morphology in comparison to flat morphology typical of cells in two-dimensional (2-D) monolayer cultures. Morphological differentiation characterized by neurite extension and cell aggregation was observed for both 2-D and 3-D cultures. Differentiated IMR-32 cells failed to develop a resting membrane potential typical of excitable cells. Free intracellular calcium was monitored with Calcium Green-1. Depolarization-induced Ca2+ influx was only observed with differentiated 3-D cells unlike 2-D cells, where calcium flux was observed in both differentiated and undifferentiated cells. Taken together, the results revealed that collagen hydrogels (0.5mg/ml collagen) were suitable structural supports for weakly adherent cells. However, for voltage-dependent calcium channel function applications, further investigations are needed to explain the difference between 2-D monolayer and 3-D collagen-entrapped cells